Flow of two consecutive Taylor bubbles through a vertical column of stagnant liquid-A CFD study about the influence of the leading bubble on the hydrodynamics of the trailing one - J. D. P. Araújo (2013)
A detailed numerical study on the interaction between two consecutive Taylor bubbles rising through vertical columns of stagnant Newtonian liquids is reported in this work. The CFD method used is based on the VOF technique implemented in the commercial package ANSYS FLUENT. Simulations were made for a large set of flow conditions, within the laminar regime, covering a range of Morton number of 4.72 x 10(-5)-104 and an interval of Entvos number between 15 and 575. The changes in the shape of the bubbles interface were followed throughout the approach process, and the main hydrodynamic features characterizing the liquid film and the wake region of the trailing bubble were determined as the separation distance became smaller. Numerical data on the velocity ratio between the trailing and the leading bubble are presented, and two distinct regions are identified (acceleration and deceleration) in the corresponding evolution curves. The velocity ratio curves produced for several flow conditions were fitted to equations describing the acceleration and the deceleration behaviour of the trailing bubble. These equations together with the fitting parameters obtained here can be very useful to improve simulators of continuous slug flow.